EFEKTIVITAS METODE TILAWATI DALAM PENINGKATAN KEMAMPUAN MEMBACA Al-QUR'AN SISWA SDIT BINTANG TANGERANG SELATAN - Dean Hermawan; Roup; Acep Jurjani (LP2M IAI Al Khairat Pamekasan, 2021)
One of the important problems faced by Al-Qur'an teachers is overcoming the disorderly students during the teaching and learning process and overcoming the irregularity of the Koran. In order for Al-Qur'an learning activities to run smoothly, many solutions are used, namely methods. In this case the researcher wants to reveal a method of reading the Koran, namely the tilawati method. The purpose of this study was to determine the students 'ability to read the Koran, the application of the tilawati method, supporting and inhibiting factors and to determine the results of students' ability to read the Koran after the implementation of the tilawati method at SDIT Bintang Tangerang Selatan. This research uses qualitative research with a phenomenological approach. This research took place at SDIT Bintang Serpong Utara, South Tangerang. The informants in this study were the principal, teachers, staff and employees of SDIT Bintang. The data collection techniques by interview, observation, documentation and triangulation. The analysis technique used is data presentation, data reduction, and drawing conclusions. This study found that the implementation of Al-Qur'an learning using the tilawati method at SDIT Bintang has gone well in accordance with the tilawati method learning guidelines. The learning outcomes prioritize the improvement in students' reading ability of the Al-Qur'an, with stages namely learning targets, learning process, material and learning evaluation. Then the results of learning Al-Qur'an using the tilawati method are very good so that children get their own pleasure in the learning process and improve much better, this can be seen from the results of the assessment or munaqosyah that have been implemented.